Evaluation of land use-transportation systems with the Analytic Network Process - Reza Banai (Journal of Transport and Land Use)
Developments in models and methods of urban systems have increasingly drawn attention to the joint effect of land use and transportation on behavioral and policy relevance, with multicriteria evaluation of and attention to the site-level analysis of spatial impacts. In this paper, we use Saaty’s Analytic Network Process (ANP), a systems-oriented method, to contribute to the emerging methodological developments in land use and transportation systems evaluation, planning, and forecasting. The ANP is applied to the problem of light rail route selection with station area land use and property value among multiple criteria. The application shows how the analysis of land use and transportation as elements of an urban system with feedback is facilitated by the ANP with data parsimony in the ex ante estimation of site-specific, spatial-economic impacts.